DISCERNMENT OF ANTIMICROBIAL RESISTANCE AMONG HEALTH PROFESSIONALS AT A MEDICAL COLLEGE IN KOZHIKODE DISTRICT, INDIA - A QUALITATIVE STUDY - Dr. Kanniyan Binub,; Dr P Selvaraj,; Dr. Krishnaraj J.S,; Dr. Jacob George P,; Dr. Sumna V.M,; Dr. Amrutha M.S,; Dr. Rakesh Ramachandran, (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Context: Overuse and misuse of antibiotics are imparting factors to the rising global public health epidemic known as antimicrobial resistance (AMR).Aims: To determine the stumbling block to antimicrobial stewardship procedures and to yield methods for reducing antimicrobial resistance (AMR) in the organization.Settings and Design:A teriary medical college hospital in Northern Kerala,India and Cross scetional studyMethods and Material: Key informant interviews were condcuted among expert practitioners from the Department of Internal Medicine,Pharmacology and  and Microbiology from a tertiary medical college in Kozhikode, Kerala.Statistical analysis used:The data were transcribed and subjected to thematic analysis.Results: Two main themes emerged from the key findings: (1) The factors affect antibiotic stewardship:  pharmacokinetic problems, overuse, lack of surveillance, and environmental contamination; and (2) solutions to improve stewardship programs, emphasizing tactics like clinical audits, surveillance programs and utilizing advanced molecular diagnostics.Conclusions: Combating AMR necessitates a multifaceted strategy that includes better surveillance systems, appropriate diagnostic use and improved antibiotic stewardship. AMR can be considerably reduced by institutional commitment to education and policy changes.